Potential of Avocado Seed Extract (Pasea Americana) As A Corrosion Inhibitor Against Surface Roughness OF CUNITI Orthodontic WIRE - Devi, Leliana Sandra; Pridjatmoko, Dwi; Herniyati, Herniyati; Sutjiati, Rina; Joelijanto, Rudy; Ramadhani, Vanda (Jurusan Kesehatan Gigi, Poltekkes Kemenkes Semarang, 2024)
The surface roughness of orthodontic archwires is an essential factor that deter- mines the effectiveness of arch-guided tooth movement. CuNiTi-based wires are widely used in orthodontic treatment, but the oral environment can trigger corrosion of CuNiTi orthodontic wires. The tannin content in avocado seed extract can be used as a corrosion inhibitor through two working mechanisms, namely, forming a passive layer and an adsorption process. The aim of this research is to examine the effect of avocado seed extract as a corrosion inhibitor on the surface roughness of orthodontic CuNiTi wire. The as- retacngular 17 x 25 inch CuNiTi wire were taken in 4 group (1 control group soaked in artificial saliva and 3 treatment groups soaked in avocado seed extract ). Â Samples were immersed in avocado seed extract with concentrations of 1,5 g/L, 2 g/L and 2,5g/L for 7 days. For surface roughness was test Surface Roughness Average analysis. One way ANOVA test showed that there was a significant difference between the control group and all treatment groups in the surface roughness test with a value of p = 0.000. Post Hoc LSD test showed that there were no significant differences between treatment group 2 and treatment group 3 with a p value = 0.122. Providing avocado seed extract with tannin content at concentrations of 1.5 g/L and 2 g/L can reduce surface roughness on CuNiTi wire due to the corrosion process.